PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PKn PADA SISWA KELAS VIII: SMP NEGERI 2 PAKEM BONDOWOSO - WAGIYAH WAGIYAH (Mitra Pendidikan, 2022)
This classroom action research is motivated by the existence of student learning difficulties on the subject of identifying the constitution that has ever been in force in Indonesia. It is known from the results of the classical assessment that pre-action learning completeness only reached 40%. This study aims to improve the learning achievement of class VIII students on the subject of identifying the constitution. The research was conducted in the form of class 2 cycle action, involving 25 students of class VIIIB SMP Negeri 2 Pakem. The success indicator set is that 85% of students complete the KKM score of 75. The data is obtained through tests as the main data, and the distribution of questionnaires at the end of the cycle as supporting data. The results showed a significant increase in learning achievement in cycle II, namely 92% of students completed. This shows an increase of 20% from the previous cycle which reached 72% completeness. Based on the results of this study, it can be concluded that the use of problem based learning learning model is able to improve student achievement in Civics learning, the subject of identifying the constitution.